Difference between transformed and spontaneous revertant strains of Neurospora crassa - M. Schablik; A. Zsindely; J. Aradi; Zs. Fekete; G. Szabó (Fungal Genetics Reports, 1978)
Difference between transformed and spontaneous revertant strains of Neurospora crassa